Analysis of the regions flanking the human insulin gene and sequence of an Alu family member. - Bell, G I (1980)
The regions around the human insulin gene have been studied by heteroduplex, hybridization and sequence analysis. These studies indicated that there is a region of heterogeneous length located approximately 700 bp before the 5' end of the gene; and that the 19 kb of cloned DNA which includes the 1430 bp insulin gene as well as 5650 bp before and 11,500 bp after the gene is single copy sequence except for 500 bp located 6000 bp from the 3' end of the gene. This 500 bp segment contains a member of the Alu family of dispersed middle repetitive sequences as well as another less highly repeated homopolymeric segment. The sequence of this region was determined. This Alu repeat is bordered by 19 bp direct repeats and also contains an 83 bp sequence which is present twice. The regions flanking the human and rat I insulin genes were compared by heteroduplex analysis to localize homologous sequences in the flanking regions which could be involved in the regulation of insulin biosynthesis. The homology between the two genes is restricted to the region encoding preproinsulin and a short region of approximately 60 bp flanking the 5' side of the genes.